The mental health and mortality impact of death of a partner with dementia. (2nd February 2016) - Shah, Sunil M.; Carey, Iain M.; Harris, Tess; DeWilde, Stephen; Victor, Christina R.; Cook, Derek G.
Abstract : Objective: Caring for a partner with dementia and partner bereavement are independently associated with poor health. An understanding of the health effects of living with a partner dying with dementia can help optimise support. We describe health in the year before and after loss of a partner with dementia compared with other bereavements. Methods: In a UK primary care database, 2624 older individuals whose partner died with dementia during 2005–2012 were matched with 7512 individuals experiencing bereavement where the deceased partner had no dementia recorded. Results: Prior to bereavement, partners of the deceased with dementia were more likely to be diagnosed with depression (OR 2.31, 1.69–3.14) and receive psychotropic medication (OR 1.34, 1.21–1.49) than partners from bereavements without dementia. In contrast, psychotropic medication initiation two months after dementia bereavement was lower (HR 0.69, 0.56–0.85). Compared with other bereaved individuals, mortality after bereavement was lower in men experiencing a dementia bereavement (HR 0.68, 0.49–0.94) but similar in women (HR 1.02, 0.75–1.38). Prior to bereavement, those who died with dementia were less likely to receive palliative care (OR 0.47, 0.41–0.54). Conclusion: In the year before bereavement, partners of individuals dying with dementia experience poorer mental health than those facing bereavement from other causes, and their partner is less likely to receive palliative care. In the year after, individuals whose partner died with dementia experience some attenuation of the adverse health effects of bereavement. Services need to address the needs of carers for individuals dying with dementia and improve access to palliative care. Copyright © 2016 John Wiley & Sons, Ltd.